2020
DOI: 10.1038/s41598-020-71499-5
|View full text |Cite
|
Sign up to set email alerts
|

A cadaver-based biomechanical model of acetabulum reaming for surgical virtual reality training simulators

Abstract: Total hip arthroplasty (THA) is a highly successful surgical procedure, but complications remain, including aseptic loosening, early dislocation and misalignment. These may partly be related to lacking training opportunities for novices or those performing THA less frequently. A standardized training setting with realistic haptic feedback for THA does not exist to date. Virtual Reality (VR) may help establish THA training scenarios under standardized settings, morphology and material properties. This work summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…Three employed the 3D Systems Geomagic Touch [68,87,88], one used the Geomagic Touch X [89] and one used the LapMentor III surgical platform [45]. One publication customised a KUKA industrial robot with haptic feedback for surgical training [90], while three built novel haptic devices [52,91,92]. Lastly, one publication adapted an existing haptic device but did not describe it [93].…”
Section: Grounded Hapticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three employed the 3D Systems Geomagic Touch [68,87,88], one used the Geomagic Touch X [89] and one used the LapMentor III surgical platform [45]. One publication customised a KUKA industrial robot with haptic feedback for surgical training [90], while three built novel haptic devices [52,91,92]. Lastly, one publication adapted an existing haptic device but did not describe it [93].…”
Section: Grounded Hapticsmentioning
confidence: 99%
“…Moreover, as the technology is not limited by portability/wearability capabilities, they can rely upon designs aimed at providing reliable and accurate performance, making them quite adaptable for the above-mentioned healthcare cases. In the case of the applicability of haptics in remote training use cases, it is evident that challenges and limitations exist; for example, the utilisation of grounded haptic devices in surgical training like the Kuka industrial robot arm in Pelliccia et al [90] or the Lapmentor III platform [45] might be challenging to be incorporated into a remote scheme for training, but as the technology matures, other simulation techniques like haptic gloves that were observed in Butt et al [67] can aid to partially or fully transfer the IVR applications into a remote training scheme.…”
Section: How Can We Improve Ivr Training For the Industry And Make It...mentioning
confidence: 99%
“…The use of high-quality online simulations may ultimately alleviate some of the expenses and concerns regarding the use of human cadaver specimens at some schools. The use of cadavers as a teaching method may prevent some very bright and capable students from considering the healthcare field [9]. Reference [3] found that the use of three-dimensional virtual models may be more effective than traditional cadaver specimens in human anatomy teaching programs.…”
Section: Discussionmentioning
confidence: 99%
“…Латеральный контур «фигуры слезы» одновременно является дном вертлужной впадины в области её ямки. Он переходит в крышу вертлужной впадины, которая соответствует суставной поверхности [12].…”
unclassified
“…Аллотрансплантация до настоящего времени остаётся распространённым вариантом костной пластики. Использование измельчённого аллотрансплантата при небольших дефектах зарекомендовало себя как надёжный и эффективный метод [44][45][46]. Наличие обширного дефекта типов IIВ, IIIA, IIIB по W.G.…”
unclassified